Outplanting and direct seeding costs of Prosopis flexuosa var. depressa (Fabaceae) for ecological restoration - Pérez, Daniel R.; Ceballos, Cristian; Oneto, María Elena (Instituto de Ecología, A.C., 2022)
Background and Aims: The ability to carry out ecological restoration in a practical way requires considering not only the probability of success in ecological terms, but also the economic costs. As a contribution to the advancement of integrated ecological and economic studies in ecological restoration, the objectives of this work were to (i) estimate the direct costs of direct seeding and planting nursery specimens of P. flexuosa var. depressa, a species considered as “framework” of the restoration in arid zones of the Monte region in Argentina, (ii) evaluate the costs in relation to the percentages of germination and establishment in the results, and (iii) compare rural and petroleum economic scenarios.Methods: Calculations were based on direct costs. To determine the incidence of the percentage of establishment in the cost of each activity, a reduction to unit values was made (a seed or plant). The direct costs of each input or activity of sowing seeds or planting were appropriated to these units, considering mortality and multiplied by the number of specimens expected per hectare.Key results: Although the establishment in the field of nursery seedlings of P. flexuosa var. depressa is much higher than the percentage of survival in direct seeding (91% vs. 11,4%), direct seeding resulted in a cost reduction of 40% in relation to outplanting. The very notable difference in salaries in the hydrocarbon business sector vs. rural wages generates an increase of four times the total values in dollars. Conclusions: It is concluded that direct seeding should receive priority in scientific research, and technical-economic assistance for rural producers.